The Implementation of a Planting Project Method To Foster Independence In Children Aged 5–6 Years - Ozah Fauzah; Mukhlisin; Deden Purbaya (Indonesian Journal of Islamic Education and Learning, 2025)
This study was motivated by the observation that some children aged 5–6 years at RA An-Najah exhibited a reliance on teachers or peers to complete various tasks, including planting activities. The aim of this research is to describe the implementation of a project-based learning method through plant cultivation to foster children's independence, analyze the outcomes of this method on the development of independence, and identify the supporting and inhibiting factors in its application at RA An-Najah Kempek Gempol Cirebon. This study employed a qualitative approach with a case study design to explore the phenomenon holistically and in depth. Data collection techniques included participatory observation, in-depth interviews with the principal, teachers, parents, and children, as well as documentation of the project activities. The research subjects were 15 children in the B2 group, along with teachers, the principal, and parents as supporting informants. The results show that the project-based learning method was carried out in three stages: planning (preparation of planting media), implementation (planting, care, and observation), and evaluation (reflection on activities with the children). Most children showed development in the categories of Developing as Expected (BSH) and Very Good Development (BSB), with indicators including task completion, initiative, responsibility, confidence, and independent behavior. Supporting factors included teacher support, availability of materials, and parental involvement. Inhibiting factors involved children’s inconsistency, limited time, and dependency on teachers. These challenges can be addressed through patient and continuous guidance.